2022
DOI: 10.3389/fnut.2022.902986
|View full text |Cite
|
Sign up to set email alerts
|

Association between caloric adequacy and short-term clinical outcomes in critically ill patients using a weight-based equation: Secondary analysis of a cluster-randomized controlled trial

Abstract: BackgroundThere is controversy over the optimal energy delivery in intensive care units (ICUs). In this study, we aimed to evaluate the association between different caloric adequacy assessed by a weight-based equation and short-term clinical outcomes in a cohort of critically ill patients.MethodsThis is a secondary analysis of a cluster-randomized controlled trial (N = 2,772). The energy requirement was estimated as 25 kcal/kg of body weight. The study subjects were divided into three groups according to thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 44 publications
2
2
0
1
Order By: Relevance
“…20 A secondary analysis of a cluster-randomized controlled trial including 2772 critically ill patients showed that hypocaloric feeding (energy intake <70% of calculated EE) compared with energy-balanced feeding during days 3-7 after ICU admission was associated with increased 28-day mortality. 21 These results strengthen the evidence for a energy intake of 80%-100% after day 3, as suggested by the ESPEN guideline. 2 Another substudy of The Augmented Versus Routine Approach to Giving Energy Trial (TARGET) showed that augmented energy delivery (1.5 kcal/ml or 1.0 kcal/ml enteral formulas) was not associated with attenuated muscle loss or recovery of strength or function 6 months after ICU discharge.…”
Section: Energy: How To Define Targets and How Much To Supply?supporting
confidence: 80%
See 1 more Smart Citation
“…20 A secondary analysis of a cluster-randomized controlled trial including 2772 critically ill patients showed that hypocaloric feeding (energy intake <70% of calculated EE) compared with energy-balanced feeding during days 3-7 after ICU admission was associated with increased 28-day mortality. 21 These results strengthen the evidence for a energy intake of 80%-100% after day 3, as suggested by the ESPEN guideline. 2 Another substudy of The Augmented Versus Routine Approach to Giving Energy Trial (TARGET) showed that augmented energy delivery (1.5 kcal/ml or 1.0 kcal/ml enteral formulas) was not associated with attenuated muscle loss or recovery of strength or function 6 months after ICU discharge.…”
Section: Energy: How To Define Targets and How Much To Supply?supporting
confidence: 80%
“…A secondary analysis of a cluster‐randomized controlled trial including 2772 critically ill patients showed that hypocaloric feeding (energy intake <70% of calculated EE) compared with energy‐balanced feeding during days 3–7 after ICU admission was associated with increased 28‐day mortality 21 . These results strengthen the evidence for a energy intake of 80%–100% after day 3, as suggested by the ESPEN guideline 2 .…”
Section: Energy: How To Define Targets and How Much To Supply?supporting
confidence: 58%
“…Observational studies have associated a cumulative protein and energy deficit with impaired outcome of critical illness [2,3,11]. However, the results of these studies might also be explained by feeding intolerance as a marker of severity of illness [2,3,12]. In the last decade, several large RCTs have addressed the timing, route and dosage of medical nutrition therapy in critically ill patients.…”
Section: Medical Nutrition Therapy In the Icu: Evidence From Rctsmentioning
confidence: 99%
“…Tatsächlich leidet ein Großteil der intensivmedizinischen Patienten unter einer Mangelernährung [113]. Diese korreliert mit einem verlängerten Aufenthalt auf der Intensivstation, protrahierter maschineller Beatmung, vermehrten Infektionen und einer erhöhten Mortalität [55, 123,159,201]. Eine adäquate Erfassung des Ernährungsstatus, die Identifikation etwaiger Risiken einer Mangelernährung, eine sinnvolle diagnostische Überwachung und kontrollierte Ernährungstherapie sind also insbesondere aufgrund des per definitionem kritischen Ernährungszustandes von intensivmedizinischen Patienten von fundamentaler Bedeutung und für das Outcome des kritisch kranken Patienten essenziell.…”
Section: Schlussbetrachtungenunclassified